Identification of Sago-Pulp Amylolytic Bacteria and Its Utilization for Granulated Fertilizer - Hasanah, Uswatun; Ardyati, Tri; Siswanto, Dian (The Journal of Experimental Life Science, 2021)
Previous research stated that bacteria isolated from sago waste from the traditional sago industry in Palopo had the potency to produce amylase. This study aims to confirm the ability of bacteria isolated from sago pulp waste to produce amylase, evaluate the ability of these amylolytic bacteria to produce IAA fix nitrogen, identify selected bacteria, and apply selected bacteria into granules biofertilizers. Bacteria were isolated from sago pulp waste and grown on a 1% starch agar medium. The amylolytic activity was analyzed qualitatively using iodine and quantitatively using the 3,5-Dinitrosalicylic Acid (DNS) method at pH 6. Amylolytic bacteria were analyzed for IAA production using Salkowsky reagent and nitrogen fixation ability through the Serra Kit method. Potential bacteria were identified based on the similarity of the 16S rDNA sequence. The selected bacteria were grown in a 10mL NB medium, and then bacteria were inoculated and air-dried to obtain the granules. The selected bacteria were put into granules and re-isolated using the total plate count (TPC) method. Eight amylolytic bacteria were obtained from sago pulp waste. L1E isolate had the highest amylolytic activity of 1.228 U.mL-1, and L1D isolate had the highest IAA production of 69.8 g.mL-1. Isolate L1E was identified as Alcaligenes faecalis with a 99.45% similarity index, and L1D was identified as Serratia surfactantfaciens with a 99.09% similarity index. Isolate L2G was identified as Alcaligenes aquatilis with a similarity index of 99.8% of the 16S rDNA sequence. The viability of bacteria from granules was 1.41 x 108 CFU.g-1.Keywords: Amylase enzyme, amylolytic bacteria, granulated fertilizer.